2014
DOI: 10.1103/physrevb.90.024105
|View full text |Cite
|
Sign up to set email alerts
|

Special quasirandom structures to study the(K0.5Na0.5)NbO3random alloy

Abstract: The local structure of K0.5Na0.5NbO3 is investigated using first-principles methods with an optimized special quasirandom structure (SQS). Through a comparison of the computed pair distribution functions with those from neutron powder diffraction data, the SQS approach demonstrates its ability to accurately capture the local structure patterns derived from the random distribution of K and Na on the perovskite Asite. Using these structures, local variations in Na-O interactions are suggested to be the driving f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…These distortions, which relieve the tensile Na-O bond strain caused by the oversized [NaO 12 ] cages, result from Na displacements along the c -axis toward the O1 atoms (Fig. 2b), in accord with the theoretical predictions 28 . The magnitude of the Na off-centering in this direction, which is twice that of K, decreases from ≈0.26 Å for x  = 0.47 to ≈0.21 Å for both x  = 0.53 and x  = 0.58.…”
Section: Resultssupporting
confidence: 83%
“…These distortions, which relieve the tensile Na-O bond strain caused by the oversized [NaO 12 ] cages, result from Na displacements along the c -axis toward the O1 atoms (Fig. 2b), in accord with the theoretical predictions 28 . The magnitude of the Na off-centering in this direction, which is twice that of K, decreases from ≈0.26 Å for x  = 0.47 to ≈0.21 Å for both x  = 0.53 and x  = 0.58.…”
Section: Resultssupporting
confidence: 83%
“…To construct our supercell model we employed the special quasirandom structure (SQS) approach to define a random arrangement of cations 51 . Previously, we demonstrated that this approach was able to properly capture the atomic distortions present in a disordered, perovskite solid solution 52 . A Monkhorst Pack k -point grid of 2 × 2 × 2 was used for the Brillouin zone integration during structural optimization.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, using SQS it is possible to gain insights into the driving mechanisms behind the transition between the lowtemperature and high-temperature phases of the (K 1=2 Na 1=2 ) NbO 3 solid solution. 54 Additionally, predictions of phase stability point to potentially synthesizable regions of the Bi (Zn,Ti)O 3 -La(Zn,Ti)O 3 -PbTiO 3 phase diagram 34 (some of which have already been confirmed by experiment).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, using the SQS approach we examined the high temperature (R3c) and low temperature (Pm) phases of the KNbO 3 -NaNbO 3 (KNO-NNO) solid solution. 54 Similar to PZT, KNO-NNO shows a significant enhancement in piezoelectric response at a composition near (K 0:5 Na 0:5 )NbO 3 (KNN) 55 and therefore has been considered to be an excellent starting structure for designing high-response, lead-free, electroceramics. [56][57][58] Given the relative chemical similarities between K and Na, it is anticipated that these cations will be distributed randomly on the perovskite A-site.…”
Section: Modeling Solid Solutionsmentioning
confidence: 99%